Single-cell multiomics analyses of spindle-transferred human embryos suggest a mostly normal embryonic development - Qi, Shuyue; Wang, Wei; Xue, Xiaohui; Lu, Zhuo; Yan, Jia; Li, Yunfei; Zhang, Yu; Shu, Mingming; Song, Chunlan; Wang, Qihang; Chuai, Yunhai; Zhai, Xinyu; et al. (PLOS Biology, 2022)
Uncoupling of the inheritance of mtDNA and the nuclear genome by spindle transfer could prevent the transmission of mtDNA mutations. Systematic single-cell multiomic analyses of spindle transferred human embryos suggest this technique seems generally safe for human embryonic development and deserves further scientific evaluation and clinical testing.